Soil Health and Biodiversity Is Driven by Intensity of Organic Farming in Canada - Lynch, Derek Henry (Frontiers in Sustainable Food Systems, 2022)
Organic farming is continuing to expand in Canada, with close to 6,000 producers farming over 2% of all agricultural land. There is insufficient evidence, however, of a trend towards larger average farm size and increasing specialization by these organic farms. This mini-review postulates that a gradient of intensity of farm management exists within organic farming sectors in Canada, with respect to cropping diversity, and tillage and nutrient utilization, and this gradient of intensity is a key determinant of agroecological outcomes. This variation in management approach and intensity reflects producer’s individual perspectives on organic farming principles and practices, irrespective of farm scale. By directly influencing farm crop and vegetative diversity and cover, and farm nutrient status and carbon cycling, management intensity determines soil carbon storage and flux, soil health and biodiversity agroecological and ecosystem services, plus farm agronomic resilience. Demographic trends and perspectives of new entrants in organic farming are encouraging signs of an increasingly inclusive and socio-ecologically complex Canadian organic farming sector, which recognizes the agroecological implications of intensity of organic farm management across all production sectors.